Postal Service Coverage Mapping For Government Performance Evaluation - Sumarno; Ira Indrarini (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The Government of Indonesia aims to provide postal services to 63% of sub-districts, with a target of 74% by 2024. This research aims to map the extent of postal service coverage in Indonesia. It is crucial to map postal service coverage in order to evaluate service performance using the network analysis - service area analysis method. The results of the study show that the postal service has not yet achieved the set coverage target in the three measured radii. Although there has been some improvement at a larger radius, a significant number of sub-districts still lack postal service coverage. At a radius of 2.5 km, only 66% of sub-districts have access to postal services, rising to 71% at a radius of 5 km and reaching 79% at a radius of 10 km. The Java region is the best performer, with only 211 subdistricts or 10% of the total subdistricts lacking postal services. In Papua, on the other hand, only 10% of sub-districts are covered, leaving about 90% without access to postal services. These study results could help inform decisions on target achievement and expansion of postal services to best meet performance targets by 2024